Evaluating the Election Law in Indonesia for Strengthening Democracy and Ensuring Honest and Fair Elections - Huda, Uu Nurul; Arifin, Firdaus; Susanto, Anthon F; Abdullah, Mohd Kamarulnizam (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2025)
Indonesia’s electoral law established the framework to uphold democracy through free and fair elections. However, its implementation faces structural and procedural weaknesses that undermine effectiveness and public trust. This study employs a legal approach to examine these weaknesses, problems, and propose corresponding reforms. Key issues include overlapping authority among the General Elections Commission, the Election Supervisory Agency, and the Election Organizer Ethics Council; weak campaign oversight due to limited resources; unclear legal definitions; lenient sanctions for violations; and challenges in enforcing strict reporting deadlines. Additionally, systemic problems such as the open-list proportional system and the presidential threshold restrict political competition and foster transactional politics. To address these, the study recommends legal and institutional reforms: clarifying institutional roles, enhancing inter-agency coordination, strengthening campaign finance regulation with digital transparency systems, and improving enforcement mechanisms and sanctions. Further, revising the electoral system and threshold requirements, alongside introducing merit-based recruitment and whistleblower protections, are proposed to ensure inclusiveness, accountability, and democratic integrity. These measures aim to create a transparent, fair, and credible electoral process that reinforces democratic principles in Indonesia.